TI_GERICHTE 52.2023.131 vom 8. November 2024 , Licenza edilizia per il cambiamento di destinazione a residenza secondaria - TI Tribunale d'appello (2024)
Licenza edilizia per il cambiamento di destinazione a residenza secondaria